Induction of callus and somatic embryogenesis from explants of Parkiabiglobosa (Jacq.)Benth and ParkiaroxburghiiG.Don. - Abouzeid, Dr Hanaa; Ahmed, Engy M; Sallam, Reda A; Kandil, Zeinab A; Tadros, Soad H; Kawy, Mostafa A. Abdel (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Legumes are very important species including herbs, shrubs and trees, they are cultivated worldwide for different economic uses.Parkiais genus belongs to the Legumefamily, Fabaceae. The most common known species are P. biglobosaBenth (African locust bean) and P. roxburghii (Tree Bean)which were introduced to Egypt since 1890. The population of the tree is rapidly declining as result conservation efforts is needed to prevent it from extinction. In an attempt to conserve this genetic resource, tissue culture studies were carried toestablish a callus culture of both plants from different explants and regeneration of the developed callus and to study the effect of explant type, media composition on the callus production and the regeneration. Apical bud,axillary bud and root explants from in vitro germinated seedlings of P. biglobosaBenthwere cultured on MS and B5 medium supplemented with (0.4., 0.8, 1.2, 1.6 or 2.0 mg l-1 NAA) + Glutamine 0.5 mg l-1 + Proline 0.5 mg l-1 + Casein 0.3 mg l-1 + 2,4D 2.5 mg l-1. Each medium was supplemented with 30 g l-1 sucrose, 3 g l-1 agar and PH 5.8.for callus induction .and (0.4.,0.8,1.2,1.6 or 2.0 mg l-1 NAA) + Glutamine 0.5 mg l-1 + Proline 0.5 mg l-1 + Casein 0.3 mg l-1 + 6-BAP 2 mg l-1. Each medium was supplemented with 30 g l-1 sucrose, 3 g l-1 agar and PH 5.8.for regeneration.The study presented here demonstrates the successful attempt at regeneration of plantlets of P. biglobosaBenth via indirect organogenesis.It can be concluded that the medium composition has a significant effect on the calli production together with the type of the explant which showed relatively higher significance. Seeds germination stage apical bud explants media 8 followed by media 10 showed the most favorable mean performances values for the studied characters, Number of days to callus initiation (day) , Callus weight (mg), Dead calli percentage (%),Albino plants percentage (%),Green plants percentage (%) and Root percentage (%). Moreover, axillary bud, showed remarkable increase in the mean performance of average. However, the overall response of MS medium was found to be superior to that of B5 medium. Explants cultured on MS medium fortified with combinations of 2,4-D and BAP induced rapidly proliferating calli that turned more friable and nodular.